The European Union, its Economic and Monetary Union, and the (Apparent) Perception of Crisis Reflected in Immediate Regulatory Actions - Nowak-Far, Artur (Polish Review of International and European Law, 2020)
While neither its institutional, nor legal arrangements fundamentally contributed to the emergence of the Eurozone crisis in the late 10’s of the 21st Century, the crisis exposed significant weaknesses of the EU economic governance, especially its inability to achieve a sustainable level of budgetary discipline. The crisis in particular highlighted the existing divisions of the EU Member States into different integration groups having divergent interests. Notably, it sharpened the division between the Eurozone states and non-Eurozone ones, as well as between the creditor-countries and debtor-countries. The EMU reform agenda adopted after 2008 gave more weighting to the interests of the former states. The emerging post-2008 economic governance-reform arrangements also gave more weight to the ECOFIN Council, at an expense of the European Commission. In the resulting institutional setting, the main aim of the EMU reform agenda was to assure the stability of the Eurozone and to reinforce its resistance to economic shocks. In this context, however, benefits arising from the reformed EMU are unevenly distributed, as they are more likely to avail the Eurozone countries than non- Eurozone countries, and more the creditor countries than the debtor ones.